Differences between 1999 and 2010 across the 1 Falkland Plateau: Fronts and water masses ... - Pérez-Hernández, M. Dolores; Hernández-Guerra, Alonso; Comas-Rodríguez, Isis; Benítez-Barrios, Verónica M.; Fraile-Nuez, Eugenio; Pelegrí, Josep L.; Naveira Garabato, Alberto C. (SEANOE, 2017)
Data used in the Paper cited. It includes CTD data in .mat format from the Moc-Austral (2010) and ALBATROS (1999) cruises. ...